How to digitise bridge structures - a systematic review of the status quo for creating digital building information modelling of existing bridge structures in the operational phase - Jäkel, Jan‐Iwo; Heinlein, Eva; Gölzhäuser, Peter; Kellner, Maximilian; Klemt-Albert, Katharina; Reiterer, Alexander (2025)
Abstract: In recent decades, the condition of many bridge structures has deteriorated and the need for maintenance measures has increased. Until now, these maintenance measures have mainly been carried out manually and reactively. The use of digital 3D models based on Building Information Modelling (BIM) can remedy this situation and create the basis for predictive maintenance management. While the generation of 3D models of new bridge structures is simple, the digitization of existing structures can be a complex process. This article provides an overview of the state of the scientific practice with regard to the procedures, technologies and data used to generate 3D models of existing bridge structures using the BIM method. Using a systematic literature analysis, scientific databases are searched for suitable literature and analysed with predefined filtering parameters. The results provide a uniform understanding of the current status quo of the digitisation of existing bridge structures and show existing degrees of digitisation and automation